Digital hostility, internet pile-ons and shaming: A case study. (December 2022) - Thompson, Jay Daniel; Cover, Rob
Digital hostility poses a grave risk to the health and wellbeing of its targets. This study addresses digital hostility levelled at public figures, and does so through the case study of Wilson Gavin. Gavin had cultivated a minor public profile in Australia through his conservative activism. In January 2020, after protesting at a drag storytelling event in Brisbane, Gavin was subject to significant online abuse; a day after the protest, he died by suicide. This study examines the forms, themes and frameworks of that abuse as it played out across a small sample of publicly available Twitter posts. The study also addresses Twitter responses to the death. These responses are significant in that they individualise Gavin's suicide and portray him as unable to protect himself and thus inherently vulnerable to taking his own life. Conversely, the study suggests that Gavin's death points to the need for an understanding of how digital hostility harms those who are subject to it and how public figures can become resilient to that hostility.